2018
DOI: 10.1037/xhp0000544
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic whole number bias in humans.

Abstract: Humans have great difficulty comparing quotients including fractions, proportions, and probabilities and often erroneously isolate the whole numbers of the numerators and denominators to compare them. Some have argued that the whole number bias is a compensatory strategy to deal with difficult comparisons. We examined adult humans' preferences for gambles that differed only in numerosity, and not in factors that influence their expected value (probabilities and stakes). Subjects consistently preferred gambles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As expected, we found that the bias changes with the probability of observing a large numerator in the larger fraction. Perhaps more interesting, we replicated previous findings that the bias persists in the balanced 50/50 condition (Alonso-Diaz et al, 2018;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012). It is a common but strange result for the adaptation theory: with balanced probabilities, the bias should disappear, i.e., picking based on the numerator will lead to chance-behavior.…”
Section: Prior Beliefs As a (Partial) Explanation For Numerator Stratsupporting
confidence: 85%
See 3 more Smart Citations
“…As expected, we found that the bias changes with the probability of observing a large numerator in the larger fraction. Perhaps more interesting, we replicated previous findings that the bias persists in the balanced 50/50 condition (Alonso-Diaz et al, 2018;Fabbri, Caviola, Tang, Zorzi, & Butterworth, 2012). It is a common but strange result for the adaptation theory: with balanced probabilities, the bias should disappear, i.e., picking based on the numerator will lead to chance-behavior.…”
Section: Prior Beliefs As a (Partial) Explanation For Numerator Stratsupporting
confidence: 85%
“…For instance, in fractals, there is self-similarity regardless of scale. If the independence of object size and ratios marks our visual experience, then the whole-number bias may be grounded on perceptions, making it universal and perseverant (Alonso-Diaz, Cantlon, & Piantadosi, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, for the ratio 15/30, people may think about the numerator, 15, or the denominator, 30, as whole numbers in isolation rather than as parts of a ratio (15/30 = ½ = 50% = 0.50). People of different ages (Alibali & Sidney, 2015; Braithwaite & Siegler, 2018; Fazio et al, 2016; Fitzsimmons et al, 2020; Ni & Zhou, 2005; Opfer & Devries, 2008), expertise levels (Obersteiner et al, 2013), and cultures (Alonso-Diaz et al, 2019; DeWolf & Vosniadou, 2015; Gómez et al, 2015; Van Hoof et al, 2020) make WNB errors. Reasoning about the magnitude of ratios compared to whole numbers is more effortful, error-prone, and time-consuming (e.g., Fazio et al, 2014; Siegler et al, 2011; Yu et al, 2020).…”
Section: Worked Example Interventionmentioning
confidence: 99%